The Labour Party, Feminism and Maureen Colquhoun's Scandals in 1970s Britain - Sarah Crook (Contemporary British History, 2020)
Maureen Colquhoun (1928-) was the Tribunite Labour MP for Northampton North during the turbulent period of Labour government between 1974 and 1979. An avowed feminist, she praised the women’s liberation movement in parliament and introduced bills that brought feminist issues to parliamentary attention. Britain’s first openly lesbian MP, she was outed by the Daily Mail in 1976 and passionately defended her relationship and the rights of gay women. Her period in parliament was marred by personal and political scandal: after she appeared to show sympathy with Enoch Powell—a position that she quickly distanced herself from—her local constituency party sought to deselect her, triggering a fight that brought Colquhoun and her supporters before the Labour Party’s National Executive Committee. This article draws upon archival records, Colquhoun’s autobiography of her time in parliament, and newspapers to explore the fraught relationship between feminism, lesbian women and the Labour Party in the 1970s. Beyond this, this research treats parliament as a site of feminist activism, alongside and in dialogue with the grass-roots activities of the women’s liberation movement in this period.